Relieve your tired eyes. - Barclay L (Life Extension, 2009)
Physicians are seeing a growing number of eye fatigue cases created by computer overuse and aging. New studies show that a natural carotenoid can protect against eye strain while combating UV damage and vision-robbing diseases.